Uso de bioestimulantes no tratamento de sementes de soja - Weber, Fernanda (2010)
The use of quality seeds and the use of products that enable improvement of their performance in the field, are important elements for a high agricultural production. Biostimulants are plant growth substances that can act alone or in comination to promote plant development. Through these substances it is possible to influence many physiological and/or morphological processes such as germination, vegetative growth, flowering, fruiting, senescence and abscission. This interference can occur by the application of these substances on seeds, soil or leaves. In such a way that needs to be absorbed to performance its role. The aim of this study was to evaluate the effect of "biostimulant" use in early treatment of soybean seeds. Seed samples treated 15 and 5 days before the day of sowing and in the day of sowing with the product "FERTIACTYL LEG® were used. These samples were sent to laboratory and were submitted to germination, vigor and root length tests. The experiment was conducted at the Laboratory of the Research Support Foundation of the West of Bahia and the samples were subjected to germination and vigor tests in the Seed Analysis Laboratory Sol (LASSOL), located in Barreiras/BA.